Kampanye Gerakan Lingkungan dan Aktivisme Online di Media Sosial (Studi Kasus Pada Aktivisme Sustainable Fashion di Media Sosial Instagram) - Nurindah Zahra Harya Puspa; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The purpose of this study is to find out whether the forms of online activism carried out in social media are manifested in actual forms of activism in the real world (offline), and see the continuity and extension of online activism from Setali Indonesia, Tukar Baju, and Kekno Klambimu in actual activism, specifically about sustainable fashion movement in Indonesia. The results show that currently the three organizations appear as advocates to spread education, messages and awareness related to sustainable fashion through Instagram, which is followed by an extension of activism in the form of offline events in the real world. In this study, the use of Instagram social media has not been effective enough to bring up mass mobilization for collective action and resource mobilization. Sustainable fashion in the perspective of Instagram users has been effecting on cognitive and affective aspects, with positive responses and impressions. Meanwhile, in the behavioral aspect, only a few informants have fully implemented sustainable fashion in a sustainable manner in their daily life.